Sequence-lithofacies paleogeographic evolution and its control on deep and ultra-deep reservoir types: A case study of the Permian Maokou Formation in northeastern Sichuan Basin. - Xiandong Wang; Wancang Tan; Peng Lu; Ying Wang; Qiang Li; Liang Zhao; Pengfei Niu; Zhengyi Cang; Bao Gong; Jiagang Shen (PLoS ONE, 2025)
The Middle Permian Maokou Formation in northeastern Sichuan Basin has been explored with continuous breakthroughs in recent years, but its sequence-lithofacies paleogeographic characteristics and tectonic-sedimentary evolution process are still unclear. Based on outcrops, well logging and seismic data, this paper focuses on the sequence stratigraphic, lithofacies paleogeography and tectonic-sedimentary evolution of the Maokou Formation in northeastern Sichuan Basin. The results show that two third-order sequences (SQ1, SQ2) are developed in the Middle Permian Maokou Formation. SQ1 can be divided into three fourth-order sequences (SQ1-1, SQ1-2, and SQ1-3). SQ1-1 and SQ1-2 are generally carbonate ramps, SQ1-3 turns to rimmed carbonate platform, and its stratigraphic thickness and sedimentary facies are distributed in NW-SE direction. The succession development of carbonate platform in SQ2 sedimentary period. It is believed that, due to the NE-trending extensional stress generated by the continuous subduction of the Mianlue Ocean and the regional sea level eustacy, the Permian tectonic-sedimentary differentiation in the northeastern Sichuan Basin had begun from the early stage of the Middle Permian and gradually intensified. As a result, the platform-basin dominated deep-water deposits gradually expanded into the basin along SW-NE direction, and evolved into the features of "platform in the south and platform-basin in the north" at the end of the Maokou Formation deposition. As such, large-scale high-energy shoals are developed above the platform region during the SQ1-3 and SQ2 depositional periods, making it a prospect of conventional gas. Potential source rocks are developed in the platform-basin region, which is a potential prospect of unconventional oil and gas. The results suggest that the tectonic-sedimentary differentiation induced by the continuous subduction of Mianlue Ocean makes the Maokou Formation an ideal reservoir for both conventional and unconventional hydrocarbon.